IMPORTANCE OF RISK FACTORS IN THE EFFECTIVENESS OF MEDICATION THERAPY IN PATIENTS WITH FUNCTIONAL LOWER EXTREMITY ISCHEMIA - Damnjanovic, Zoran; Sarac, Momir; Stepanovic, Nemanja; Jovanovic, Nemanja; Milic, Dragan (Acta medicae Medianae, 2024)
Analysis of the influence of risk factors on drug therapy measured by prolongation of the claudication distance in patients with functional lower extremity ischemia (FLEI) can significantly improve the individual approach to the treatment of these patients.The aim of the study was to determine the impact of risk factors on the effectiveness of medicament therapy in patients with FLEI.The study included 82 patients with diagnosed FLEI (Fontaine IIa, IIb), treated at the Clinic for Vascular Surgery of the University Clinical Center in Niš, starting from January 2020 to December 31, 2020. After 6 months of examination, there was a statistically significant difference in the prolongation of claudication distance in relation to the therapeutic modality in woman (p = 0.03), patients with dyslipidemia (p = 0.001) and patients with hypertension (p = 0.02), noting that higher efficacy was achieved in the group of respondents who used cilostazol and acetylsalicylic acid (ASA).Risk factors that have a significant effect on the applied therapeutic modality are female gender, dyslipidemia and hypertension, while age, obesity and male gender are risk factors where such correlatiоn is not present. Cilostazol and ASA therapy were more effective than pentoxifylline and ASA therapy in the group of respondents suffering from hypertension and dyslipidemia as well as in women.
Keywords: risk factors, medication therapy, peripheral arterial disease